Different Effects of Ethanol and Activation of TRPM8 ION Channel on Metabolic Response to Cold - Tamara V. Kozyreva; Elena Ya. Tkachenko; Valery P. Kozaruk; Galina M. Khramova (Journal of Glycomics And Metabolism, 2016)
The possible interrelation of ethanol and the membrane protein molecules such as TRP ion channels in the whole living organism has not been studied. In the present research we study the influence of ethanol (50%) and agonist of TRPM8 ion channel L-menthol (1% in 50% ethanol) application to abdominal skin on the thermoregulatory response to cooling in rats. We used two types of cooling with the different rates of skin temperature decrease - 0.1 °C/sec for rapid and 0.005°C/s for slow cooling. It was shown, that the effects of ethanol and activation of the cold-sensitive TRPM8 ion channel are mainly directed at different components of thermoregulatory metabolic response to cold. Menthol, as an agonist of the TRPM8 ion channel, besides the constrictor vascular response stimulates predominantly the emergency first phase of metabolic response which appears only at rapid cooling without any effect on the second phase of metabolic response to cooling. Ethanol inhibits the most powerful second phase of metabolic response to cold which is manifested at decreased deep body temperature and is associated with the development of not only non-shivering but also shivering thermogenesis. Effect of ethanol is accompanied by the acceleration of the deep body temperature fall. Ethanol does not prevent the effect of menthol on thermoregulatory blood vessel and emergency phase of metabolic response, and the activation of the cold-sensitive TRPM8 ion channel by menthol has no obvious influence on the effects of ethanol – inhibition being the most powerful thermogenic component of the metabolic response to cold.
Keywords: TRPM8 ion channel